Instructions to Prospective Authors by Indian Biomedical Journals: An Opportunity to Promote Responsible Conduct of Research. (April 2017) - Bhat, Anup; Shah, Akash; Sherighar, Swathi G.
Journals provide instructions to prospective authors to facilitate the process of manuscript publication. The information provided under such instructions could be a potential opportunity to promote responsible conduct of research (RCR). We analyzed 74 Indian biomedical journals for the type of information provided in the "instructions to authors" section and adherence to the International Committee of Medical Journal Editors (ICMJE) recommendations. Among the 71 journals that had an "instructions to authors" section, 53 journals adhered to ICMJE recommendations. We discuss sections of the ICMJE recommendations detailed by Indian biomedical journals under the "instructions to authors" section and emphasize components that require greater exposure.